Pengaruh Letak Biji Pada Buah Terhadap Viabilitas dan Pertumbuhan Tanaman Pepaya (Carica Papaya l.) - Novita Sarlince Susanti Ina; Bagus Putu Udiyana; I Made Suryana; Komang Dean Ananda; I Made Sukerta (Program Studi Agroteknologi Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Papaya plant (Carica papaya L) is one of the plants whose natural habitat is tropical forests and papaya is also one of the introduced fruit that has long been known and developed widely in Indonesia. The germination of seeds at the beginning of seed formation is very low, but as the age of the seeds increases, which is associated with the accumulation of food reserves, the ability of seeds to germinate increases. The older the seed, the dry matter content in it will be higher. The dry matter content is the accumulation of food reserves formed through the process of photosynthesis. The purpose of this study was to find out where the seeds of papaya plants are located which produce good viability and growth and also to find out from the layout of the seeds (base, middle, tip) the seeds that grow the fastest. The design used in this study was randomized block design (RAK), with treatment of the location of seeds on papaya as many as 3 factors with 9 replications so that the total number of treatments was 27 polybag pots. The treatments were the location of the seeds from the tip (Bu), the middle (Bt), and the base (Bp). The results showed that the treatment of the base (Bp) resulted in a fast growth rate of 13.89 (hst), plant height 14.69 (cm), number of leaves 11.22 (strands), plant fresh weight 7.40 (g) and plant oven dry weight 4.57 (g). ). So from the results of this study the treatment of the base (Bp) which resulted in the best growth compared to the treatment of the tip (Bu) and the middle part (Bt).